[The Sailors and Soldiers Club, Trinidad, B.W.I.] - (:unkn) unknown (My University, 2010)
This postcard shows the Sailors and Soldiers Club which was opened 14 June 1922 and which ran until 1957 as tribute to the Trinidad Merchants and Planters (white) Contingent who served as troops for Britian in Europe in World War I (1914-18). The building located south east Belmont Circular Road and Queen's Park Savannah was a large, two-story structure with an annex. It was designed by Dr. Maxwell Johnstone. The building later became the Central Library and when the Library moved, it was left to decay and was finally demolished in 1984.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Buildings--Trinidad and Tobago; Bars (Drinking establishments)--Trinidad and Tobago; [1922]; Palms--Trinidad and Tobago; Fences--Trinidad and Tobago; Windows--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Clubs--Trinidad and Tobago; Wooden windows--Trinidad and Tobago; Arches--Trinidad and Tobago; Architecture--Trinidad and Tobago; Soldiers--Trinidad and Tobago; Armed Forces--Trinidad and Tobago; Sailors--Trinidad and Tobago